(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2012)
This study analyzes a recent ruling by the Superior Court of Justice, which annulled a case in which the judge, in the absence of the Public Prosecutor’s representative, asked questions of the prosecution witness. In addition to criticizing the Superior Court’s position, a reflection is made on the principle of real truth.